Adakites, High-Nb Basalts and Copper–Gold Deposits in Magmatic Arcs and Collisional Orogens: An Overview - Pavel Kepezhinskas; Nikolai Berdnikov; Nikita Kepezhinskas; Natalia Konovalova (Geosciences, 2022)
Adakites are Y- and Yb-depleted, SiO2- and Sr-enriched rocks with elevated Sr/Y and La/Yb ratios originally thought to represent partial melts of subducted metabasalt, based on their association with the subduction of young (<25 Ma) and hot oceanic crust. Later, adakites were found in arc segments associated with oblique, slow and flat subduction, arc–transform intersections, collision zones and post-collisional extensional environments. New models of adakite petrogenesis include the melting of thickened and delaminated mafic lower crust, basalt underplating of the continental crust and high-pressure fractionation (amphibole ± garnet) of mantle-derived, hydrous mafic melts. In some cases, adakites are associated with Nb-enriched (10 ppm < Nb < 20 ppm) and high-Nb (Nb > 20 ppm) arc basalts in ancient and modern subduction zones (HNBs). Two types of HNBs are recognized on the basis of their geochemistry. Type I HNBs (Kamchatka, Honduras) share N-MORB-like isotopic and OIB-like trace element characteristics and most probably originate from adakite-contaminated mantle sources. Type II HNBs (Sulu arc, Jamaica) display high-field strength element enrichments in respect to island-arc basalts coupled with enriched, OIB-like isotopic signatures, suggesting derivation from asthenospheric mantle sources in arcs. Adakites and, to a lesser extent, HNBs are associated with Cu–Au porphyry and epithermal deposits in Cenozoic magmatic arcs (Kamchatka, Phlippines, Indonesia, Andean margin) and Paleozoic-Mesozoic (Central Asian and Tethyan) collisional orogens. This association is believed to be not just temporal and structural but also genetic due to the hydrous (common presence of amphibole and biotite), highly oxidized (>ΔFMQ > +2) and S-rich (anhydrite in modern Pinatubo and El Chichon adakite eruptions) nature of adakite magmas. Cretaceous adakites from the Stanovoy Suture Zone in Far East Russia contain Cu–Ag–Au and Cu–Zn–Mo–Ag alloys, native Au and Pt, cupriferous Ag in association witn barite and ...